Innovative low-cost vibration monitoring system to unleash the power of condition monitoring - Kamble, Brahmadeo; Patil, Manish (PREPARE@u® | IEI Conferences, 2021)
This case study deals with the technical solution and economic impact of machine condition monitoring implemented on Okuma CNC Machine, RMC mixer, and CTX 310 CNC machine It presents an overview of the measuring techniques used to detect machine problems and very briefly describes condition monitoring system tailored to the special requirements of CNC machines and RMC mixer gear boxes.